The english language learning inside the escuela activa urbana model in a public school: a study of sixth graders (2008)
This study reports the findings of research dealing with sixth-graders’ perceptions of English language learning and the impact of active learning approaches in a public school in Manizales, Colombia. Participants in the research were involved in lessons planned according to the principles of task-based learning and active learning, inside the Escuela Activa Urbana model implemented by some private and public institutions in this city. The findings reported a positive impact of the model on the language learning process which was reflected in the increase of students’ participation, language production, and class interaction. Key words: English as a foreign language, task-based learning, active learning, teamwork Este estudio reporta los hallazgos de una investigación sobre las percepciones del aprendizaje de la lengua inglesa por parte de alumnos de sexto grado y el impacto de enfoques de aprendizaje activo en un colegio público en Manizales, Colombia. Los participantes en la investigación tomaron parte en clases planeadas de acuerdo con los principios del aprendizaje basado en tareas y de las metodologías activas en el marco del modelo Escuela Activa Urbana implementado por algunas instituciones públicas y privadas de la ciudad. Los hallazgos reportan un impacto positivo del modelo en el proceso de aprendizaje de la lengua el cual se refleja en el incremento de la participación, la producción lingüística y la interacción de los estudiantes. Palabras clave: Inglés como lengua extranjera, aprendizaje basado en tareas, aprendizaje activo, trabajo en equipo